Economic Policy Uncertainty and Cost of Debt Financing in Indonesia - Komari, Nadya; Juliana, Rita (E-Jurnal Akuntansi; Vol 32 No 4 (2022), 2022)
This study aims to see the effect of Economic Policy Uncertainty (EPU) to the cost of debt in Indonesia. This quantitative research sample used in this study includes a total of 4,312 observations collected from 453 listed firms on IDX from the period 2006 to 2020. Using fixed-effect panel data regression, our result shows that there is a positive relationship between the cost of debt and EPU, and the effect is even greater when a crisis occurs. With additional analysis conducted, our result show EPU has stronger impact on large firms’ than small firms’ cost of debt. However, when a crisis occurs, EPU has a higher effect on small firms samples than on large firms samples. Thus, it can be concluded if the crisis plays an important role in the research results. Keywords: Cost Of Debt; Economic Policy Uncertainty; Crisis.